Identifikasi Faktor – Faktor Kepuasan Pengguna Terhadap Layanan Website Universitas ABC Menggunakan Metode IPA - Dorie Pandora Kesuma; Rika Kharlina Ekawati (Universitas Katolik Musi Charitas, 2019)
This study aimed to identify the factors user satisfaction of ABC University website service with Importance Performance Analysis (IPA) method. IPA is used to measure the level of user satisfaction with the services provided. The population in this study was all students at ABC University, where the number of samples taken about 200 respondents. The method survey that was analyzed by IPA (Importance Performance Analysis) to determine the level of customer satisfaction that is the gap between importance and performance. The results showed that of the 27 attributes were analyzed by IPA grouped into quadrant I (7 attributes), quadrant II (8 attributes), quadrant III (5 attributes) and quadrant IV (6 attributes).